Setting and Strategy Child Friendly Classroom Management in Early Childhood Education: A Literature Review - APRILIA, ELSA FIRDA (Exploration in Early Childhood Research, 2024)
Creating and maintaining a safe and comfortable learning environment has a very important role in preventing bullying in early childhood education. Teachers can implement child-friendly classroom management to create a safe and comfortable environment. This research uses a type of qualitative research with a library study method or known as a literature review such as journals and scientific articles. The result is that child-friendly classroom management has been proven to be more practical and effective in Early Childhood Education classes. Through child-friendly classes, children's acceleration and abilities can be improved because the child-friendly learning process has consistent values and is in line with children's needs. In addition, creating a friendly classroom can reduce aggressive behavior and increase prosocial behavior among students. A child-friendly education system has also been implemented in New Zealand by integrating contextual learning that is relevant, interesting and meaningful. The role of teachers in child-friendly classroom management is very important. Teachers as role models in the classroom can foster a friendly learning environment to overcome bullying behavior in children. However, good pedagogical competency support is also needed so that teachers can create a more positive learning atmosphere. The importance of creating child-friendly classes in early childhood education is to provide a classroom environment that is safe, comfortable, and supports children's optimal development. Classroom arrangements can be made by arranging classrooms that are safe, easily accessible, comfortable and clean, providing safe and interesting learning media, and ensuring positive communication between teachers and children.